Development of a Problem-Based Learning Model in Islamic Religious Education to Enhance Students’ Critical Thinking Skills - Hapni Laila Siregar; Nurmayani Nurmayani; Junaidi Junaidi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This research aims to create a problem-based learning model for Islamic Religious Education (PAI) with the goal of enhancing students’ critical thinking abilities. Critical thinking is an essential skill that enables students to successfully address the challenges they encounter in both their personal and social lives in the 21st century. The importance of critical reflection is also emphasized in Islamic teachings, particularly in the Qur'an and Hadith, where numerous passages encourage contemplation (ulul albab). To foster critical thinking, it is essential to implement a learning model that promotes this skill, and problem-based learning (PBL) is identified as an effective approach. This study was conducted across various departments at Medan State University using the Research and Development (R&D) methodology proposed by Borg and Gall. The research gathered data through observations and questionnaires, with the Mann-Whitney U test used for data analysis. The results demonstrate that the problem-based PAI learning model is successful in enhancing students’ critical thinking skills. This conclusion is supported by the Mann-Whitney U test, which showed that the Asymp. Sig. (2-tailed) value was below α, leading to the rejection of the null hypothesis and the acceptance of the alternative hypothesis. Therefore, there is a statistically significant difference between the critical thinking abilities of students who participated in the problem-based PAI learning model and those who experienced traditional learning methods.